Fungsi Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Kupang Terhadap Eksploitasi Anak Dibawah Umur Sebagai Pekerja Informal - Benaya Jizhar Olyvery Kapitan; Yosef Mario Monteiro; Ivan Ndun (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Exploitation according to Law Number 35 of 2014 concerning Child Protection is divided into physical, social, sexual and economic exploitation. With the existence of children who work, this is a violation of the right to child protection and child growth and development, which should be at that age the child is still in school and gets a proper education. The phenomenon of underage labor almost occurs in all regions of Indonesia. One of the children's problems that must receive special attention is the issue of child labor. This issue has become global because so many children around the world are already working at school age. In fact, the issue of child labor is not just an issue of children carrying out work with wages, but it is very closely related to exploitation, dangerous work, inhibition of access to education and hindering the physical, psychological and social development of children, even in certain cases and forms of child labor have entered as the qualification of children who work in the most intolerable situations (the intolerable form of child labor). This research is an empirical research that uses primary data and secondary data collected using interview, observation and literature study techniques. The informants in this study are 10 people. The data processing techniques in this study use several techniques, namely editing, coding, tabulation and verification after which the data will be analyzed using qualitative descriptive techniques. The results of this study show that (1) the Kupang City Women's Empowerment and Child Protection Office needs to increase socialization, supervision, and cooperation with the community to effectively prevent and protect minors from exploitation. (2) Budget factors, apparatus resources, and socialization of child protection to the community are factors that hinder the implementation of the functions of the Kupang City Women's Empowerment and Child Protection Office in providing prevention, protection, coaching and empowerment of children.